Branded entertainment dealmaking strategies & techniques for industry professionals - Valero, Damaris 1966- (J. Ross Publishing, 2015)
Our media options have increased and evolved more in the last decade then over the last century. This evolution affects all aspects of our lives and, more specifically, has forever altered how consumers interact with the brands vying for their attention on all types of media outlets. In today's world, a brand cannot just preserve the status quo but must be positioned correctly within a tumultuous world of options for both advertisers and consumers. One of the big questions for a brand manager is whether to place the brand inside content that's created exclusively with the brand in mind? This is the idea behind Branded Entertainment (BE). It is not product placement but a concept where brands and solid, entertaining content become truly intertwined. This book provides a thorough and practical understanding of the BE business including when it makes sense and when it doesn't. It explains the roles and thought process of all parties involved in a potential deal: the brands, the networks, the content producers, and the ad/marketing agencies. Branded Entertainment outlines the many different scenarios that could surface in these arrangements depending on who leads a deal and who accepts production costs. It summarizes the do's and don'ts of this business and gives the reader a checklist of things to keep in mind when at the deal table.